Parental engagement and deficit discourses: absolving the system and solving parents. Issue 1 (2nd January 2021) - Goodall, Janet
ABSTRACT: This paper asks a series of questions to prompt critical, informed thinking around research and practice in relation to parental engagement with children's learning. The questions ask how we, who research and work in this area, acknowledge and deal with the discourse of a culture of poverty, whether and if the "private sphere" of the family indeed remains private, what may be considered "good parenting" and why. The questions go on to investigate the place (or lack of it) of gender in work around parental engagement, and looks to the future to ask what work in this field can do in the face of the inequities in society which have required the field to exist in the first place. Finally, the questions are reframed to form the basis of a new research agenda.